Mentoring for Success: Transforming Religious Tourism Management at Islamic Boarding School - Santa Rusmalita; Patmawati Patmawati; Raziki Waldan (Khazanah Sosial, 2023)
This study aims to carry out and analyze mentoring programs on optimizing the management of human resource management (HR), finance, and marketing of religious tourism at the Darul Fikri Islamic Boarding School. This research uses the Participatory Action Research (PAR) method with advisors, teachers, and students at the Darul Fikri Islamic Boarding School. Meanwhile, data was collected through observation, interviews, and the active participation of Islamic boarding school administrators and their students. The results showed that mentoring on optimizing the management of religious tourism at the Darul Fikri Islamic Boarding School was carried out in three stages: planning, implementation, and evaluation. At the planning stage, the researchers discussed with the stakeholder to determine the form of mentoring for managers, teachers, and students. While in the implementation stage, researchers carry out two types of mentoring: basic and advanced. The management theory and practice in the two mentoring include human resource management, financial management, and marketing management. Finally, at the evaluation stage, the researcher saw that this mentoring activity had achieved satisfactory results with the following indicators of success: the mentoring program was implemented well, the program's targets and objectives were achieved, the mentoring program received support from various parties, the management of religious tourism at the Darul Fikri Islamic Boarding School experienced to change for the better than before.